HIP IMPLANT ANALYSIS WITH CATIA - Florin CIOFU (Fiabilitate şi Durabilitate)
CATIA V5R16 is a product of Dassault Systemes, one of the most widely used CAD/CAM/ CAE systems worldwide, with applications in various fields, from the automotive, aerospace, automotive and medical industries. The paper aims to improve the technical, technological and medical knowledge related to the activity of the hip prosthesis.